Drinking and Domesticity: The Materiality of the Mid-Nineteenth-Century Provincial Pub. (20th April 2018) - Booth, Nathan
Abstract: Pubs in the mid-nineteenth century were ubiquitous yet ideologically divisive sites of urban leisure. Consequently, histories of drinking in this period have sometimes focused on Temperance narratives around criminality, poverty, and alcoholism over the everyday world of these establishments. The reason for the appeal and ubiquity of pubs was not simply that they offered access to alcohol and opportunities for inebriation and escapism; pubs were also sites of surrogate domesticity. This article discusses how this domesticity was manifest and how it shaped these spaces of leisure, extending our understanding of drinking establishments between the Beerhouse Act of 1830 and the wholesale pub 'improvements' of the later-nineteenth century. It focuses on non-metropolitan contexts using Stalybridge, an emergent factory town in the north-west of England, as its case study. The pubs of mid-nineteenth-century Stalybridge incorporated a strong element of domesticity in their design and layout. Drawing on auction listings, building plans, and street scenes, this article emphasises the domestic origins of the beerhouse and considers the ways in which the furniture of the pub facilitated sociability. It then uses the diaries of James Knight, a schoolmaster and frequent pub-goer in the 1850s and 1860s to uncover the importance of the pub in everyday life. They were formative sites for many young men, in particular, providing opportunities for social, intellectual and professional development – at once community hubs and personal retreats, a place for both standing a drink and sitting down to Shakespeare.